Placental-derived stem cells for dental tissue engineering: Trash or treasure/ Nur Aliana Hidayah Mohamed - Mohamed, Nur Aliana Hidayah (Faculty of Dentistry, 2014)
Stem cells are different from other cell types by two important characteristics. First, they are unspecialized cells which capable of renewing themselves through cell division. In addition, some cells are _switched-on' after long periods of inactivity. Secondly, under certain physiologic or experimental conditions, they can be induced to differentiate into any tissue type in order to carry out specific tasks. In some organs, such as the gut and bone marrow, stem cells regularly divide to repair and replace damaged tissues. In other organs, however, such as the pancreas and the heart, stem cells only divide under special conditions. Stem cells remains pluripotent and theoretically, it can be induced to differentiate into any specialized cell type of choice [6,7]. These stem cells may be candidate sources for tissue engineering, including tooth, tissue and bone regeneration